Preparation and Application of ZIF-8 Thin Layers - Martin Schernikau; Jakob Sablowski; Ignacio Guillermo Gonzalez Martinez; Simon Unz; Stefan Kaskel; Daria Mikhailova (Applied Sciences, 2021)
Herein we compare various preparation methods for thin ZIF-8 layers on a Cu substrate for application as a host material for omniphobic lubricant-infused surfaces. Such omniphobic surfaces can be used in thermal engineering applications, for example to achieve dropwise condensation or anti-fouling and anti-icing surface properties. For these applications, a thin, conformal, homogeneous, mechanically and chemically stable coating is essential. In this study, thin ZIF-8 layers were deposited on a Cu substrate by different routes, such as (i) electrochemical anodic deposition on a Zn-covered Cu substrate, (ii) doctor blade technique for preparation of a composite layer containing PVDF binder and ZIF-8, as well as (iii) doctor blade technique for preparation of a two-layer composite on the Cu substrate containing a PVDF-film and a ZIF-8 layer. The morphology and topography of the coatings were compared by using profilometry, XRD, SEM and TEM techniques. After infusion with a perfluorinated oil, the wettability of the surfaces was assessed by contact angle measurements, and advantages of each preparation method were discussed.